Helminth Parasites Found in Rhacophorid Frog, Polypedates braueri (Vogt, 1911), from Taiwan - Hasegawa, Hideo; Ota, Hidetoshi (Tropical Natural History, 2021)
Three species of nematodes, Oswaldocruzia japalurae, Cosmocerca sp. and Cosmocercella iwatsukii, and one acanthocephalan, Pseudoacanthocephalus cf. bufonis, were collected from Polypedates braueri, a rhacophorid frog native to Taiwan and the eastern part of subtropical continental Asia. Cosmocercella iwatsukii was first collected outside of the type locality on Okinawajima Island. The problem in identification of Cosmocerca parasitic in amphibians of Japan and Taiwan is discussed from a historical viewpoint.